TRAFIL: A tool for enhancing simulation TRAce FILes processing - Christos Bouras; Kostas Stamos; G Kioumourtzis; Savvas Charalambides (International Conference on Data Communication Networking - DCNET 2012, Rome, Italy, 2012)
NS-2 (Network Simulator) is one of the most popular discrete event simulators used for network simulation. Trace files produced by NS-2 provide very useful information for post simulation analysis. This paper presents the architecture and development considerations for a TRAce FILe analysis tool, which intends to simplify the management of trace files generated during network simulations. The tool is focused on NS-2 trace files, but can be extended to handle a variety of simulation trace files formats. Its purpose is to make the execution of a large number of network simulations faster, and the extraction of results from a large amount of data more flexible and productive. TRAFIL introduces a novel way of interpreting, parsing, reading and eventually utilizing NS-2 trace files by using "metafiles" and "sub-metafiles" during the trace file recognition and process procedures, making the overall operations more abstract, substantially efficient and faster than alternative approaches. Furthermore, TRAFIL facilitates the whole trace file analysis task, offering the opportunity to store each trace file as well as every measurement produced for each trace file. The tool aims to aid the analysis of simulation results offering features that other tools in this area have been missing.